L’expertise paysagère à l’épreuve de l’espace agricole périurbain - Saloua Toumi; Roland Vidal (Projets de Paysage)
In a region such as Île-de-France which is characterised by both a high demographic concentration and an major presence of agriculture, the expectations towards agrarian landscapes are numerous. Agriculture is an important actor on the food world market, but it is also called upon as a common landscape good supposed to offer a certain quality of life surrounding. Must these two expectations give place to separated territories or is it possible to conciliate productivity and landscape quality on the same territory project ? Landscapers will be more and more confronted to these questions in the years to come. Between an excessive productivity and a regress à which would be hard to accept à they will have to find the right balance in order to place the agrarian landscapes into a genuine durability.